Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Motor Honda CBR 150 R Pada PT. Maluku Graha Motor - Yohana Sopamena; Maudy M. Tanihatu; Pocerattu V. Alfonso (Jurnal Administrasi Terapan, 2024)
PT. Maluku Graha Motor is a company that engaged in automotive industry, in the form of sales and service of Honda motorbikes which are well known in Eastern Indonesia. Price and product quality strategies are ones of the factor that are expected to increase consumer purchase decision of Honda CBR 150 R motorcycle at PT. Maluku Graha Motor. The pricing strategy use the standard mark-up pricing while product quality strategy that used is motorbike appearance gets more sporty, the headlights are equipped with LED technology, the speedometer is digital, the braking quality is fairly good, the transmission and clutch are smooth, full features , good motor handling, good material quality compared to previous versions, good paint and striping quality, also fitting suspension settings. For this reason, this study aims to determine the effect of price and product quality on purchase decision for Honda CBR 150 R motorcycle at PT. Maluku Graha Motor.This type of research is qualitative and quantitative using multiple linear regression analysis tools. Based on the research results with assistant of SPSS 20 software, the regression equation Y = -3.587 + 0.086X1 + 0.678X2 was obtained. In proving the hypothesis through the results of the T test for the price variable, the T value < T table (0.523 < 2.008) and the T test for the product quality variable obtained T count > T table (4.709 > 2.008), so it can be concluded that there is no effect of price partially while there is an effect of product quality on purchase decision of Honda CBR 150 R. From the calculation results also obtained the value of r table> r count and Cronbach Alpha > 0.6Based on these results it can be concluded that price has no positive effect while product quality has positive effect on purchase decision, and submitted suggestion for PT. Maluku Graha Motor is company should be further improve purchase decision by attract customer’s interest to purchase Honda CBR 150 R motorcycle through pricing. Keywords: Price, Product Quality, Purchase Decision